ANALISIS KEBUTUHAN MATERI DALAM KURIKULUM BIPA BAGI PENUTUR TETUM DI TIMOR LESTE - Rodolfo Soares (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to identify and analyze the material needs within the Bahasa Indonesia for Foreign Speakers (BIPA) curriculum in Timor Leste, specifically from the perspective of learners whose first language is Tetum. Employing a descriptive qualitative approach, data were collected through interviews and document analysis, then examined thematically to explore linguistic needs, sociocultural dimensions, learning strategies, and instructional challenges. The findings reveal that learners struggle with abstract vocabulary, formal sentence structures, and comprehension of academic texts. They also express a strong need for audio materials, structured listening practice, and learning resources that align with their local context. The discussion highlights that culturally contextualized content such as Timorese folklore and traditional practices along with informal peer interaction and exposure to Indonesian media, significantly enhances learner motivation and confidence. However, several challenges persist, including misalignment between instructional materials and learners’ actual needs, limited speaking and listening practice, and a lack of locally relevant educational resources. Therefore, this study recommends the development of a BIPA curriculum that is adaptive, inclusive, and responsive to the sociocultural realities of Tetum-speaking learners in Timor Leste, in order to foster more meaningful and empowering language learning experiences.